Evidências preliminares da eficácia de um enxaguante bucal contendo 5% de própolis para o controle de placa e gengivite - Elizete Maria Rita Pereira (2010)
Mouthwash based on medicinal plants and propolis can be easily found in the Brazilian market even if it has not been tested in reliable clinical trials on its efficacy or possible unpleasant side effects like the ones which alter the hard and soft oral tissues. The aim of this study was to obtain preliminary evidence of efficacy of an alcohol-free mouthwash containing 5% green propolis (MGP 5%) on the control of plaque and gingivitis. Twenty-five subjects, both male and female, were chosen aftersigning the terms of agreement. These subjects are UFMG employees and individuals who would begin treatment on an extension project called Supportive Periodontal Therapy at the Faculty of Dentistry of Federal University of Minas Gerais, Belo Horizonte, from August to December 2009. The criteria for selection stated that subjects should be from 18 to 60 years old, should present good health, a minimum of 20 teeth and not be pregnant or breastfeeding. Also, they should present gingivitis with a plaque level of 1.5 or higher (Modified Quigley-Hein Plaque Index (1970) . PI) and gingivitis level of 1.0 or higher (Modified Loe-Silness Gingival Index (1977) . GI), in the beginning of the research. These subjects who wore braces, retainers or removable prosthetics, presented tumors and gingival growths by medication or not or were allergic to propolis and thus made use of antibiotics two weeks before the study, were excluded. The subjects went through a dental prophylaxis before starting rinse. They were then instructed to rinse twice a day for a minute, immediately afterbrushing (morning and night), using the 10 ml of the MGP 5%. After 45 and 90 days using the product the individuals returned for a clinical evaluation which considered changes in the soft and hard oral tissues and involved collecting plaque and gingivitis indexes. On their last appointment the subjects answered a questionnaire about their level of appreciation and acceptability of the mouthwash. Compliance with thetreatment was also evaluated through an attendance form. For the statistic analysis we used BioEstat 4.0 and Excel 2007. After the period of treatment, the PI and GI were significantly reduced when compared to the first examination (p< 0.05). The alterations found were not different from the ones related to the use of the mouthwash available in the market. Although most the individuals found the taste of MGP 5% unpleasant, they were satisfied with the product considering the positive changes and the improvement of oral health after the period of treatment. Thus, compliance with treatment was high (. 80%). The MGP 5% showed evidence of its efficacy in reducing PI and GI, with the necessity of doing a double-blind randomized clinical trial to validate such efficacy.